RELATIONSHIP BETWEEN MELOIDOGYNE INCOGNITADENSITYAND PLANT GROWTH OF OKRA - M. Hussain; M. Zouhar; P. Ryšánek; S. A. Anwar (Journal of Animal and Plant Sciences, 2016)
Root-knot nematodes (Meloidogynespp.) are the most important pests of vegetables, field crops, and ornamental plants. During our previous study, twenty eight okra cultivars were examined against resistance and Pusa Swami was ranked the most susceptible. The purpose of this study was to investigate the effects of increasing initial population density (Pi) of M. incognita on nematode reproduction and growth of susceptible okra cv. Pusa Swami in green house. Five Pi levels (250, 500, 750 and 1000 eggs) were used during experiment. Nematode reproduction was assessed by determining the number of galls, egg-masses,eggs per root system, and reproduction rateper root system. Egg-masses on Phloxine B stained roots were quantified by using stereomicroscopeand root systems were rated for galling and egg mass presence on a 0 to 5 scale where 0 = no gall or egg masses, 1 = 1-2, 2 = 3-10, 3 = 11-30, 4 = 31-100, and 5 = >100 galls or egg masses per root system. Nematode reproduction was directly proportional to initial population density (Pi). Reproduction rate (Pf/Pi, where Pf = final number of eggs / initial egg density) increased proportionately with increased Pi. Foliage growth (cm) had inverse relation to Pi whereas root growth (g), gall and egg-mass indices were significantly increased. Our results show that root weight is poor parameter to assess the effects of root knot nematode to correlate with foliage growth.
Keywords: Meloidogyne incognita; okra; plant growth parameters; Nematode reproduction parameters